2004
DOI: 10.1042/bj20031860
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of folds in animal toxins acting on ion channels

Abstract: Animal toxins acting on ion channels of excitable cells are principally highly potent short peptides that are present in limited amounts in the venoms of various unrelated species, such as scorpions, snakes, sea anemones, spiders, insects, marine cone snails and worms. These toxins have been used extensively as invaluable biochemical and pharmacological tools to characterize and discriminate between the various ion channel types that differ in ionic selectivity, structure and/or cell function. Alongside the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(181 citation statements)
references
References 61 publications
3
172
0
3
Order By: Relevance
“…The mechanisms underlying the blockade of voltage-gated K ϩ channels by ␣-KTx toxins have been intensively explored in the last decade (11,(43)(44)(45) by the modeling analysis of the toxin-K ϩ channel complex generated by docking and dynamic simulations. In order to elucidate the possible interaction mode, the three-dimensional structural model of the BmP09-BK channel complex was generated by docking and dynamic simulations (Fig.…”
Section: The Possible Interaction Mode Of Bmp09 With Bk Channel-mentioning
confidence: 99%
“…The mechanisms underlying the blockade of voltage-gated K ϩ channels by ␣-KTx toxins have been intensively explored in the last decade (11,(43)(44)(45) by the modeling analysis of the toxin-K ϩ channel complex generated by docking and dynamic simulations. In order to elucidate the possible interaction mode, the three-dimensional structural model of the BmP09-BK channel complex was generated by docking and dynamic simulations (Fig.…”
Section: The Possible Interaction Mode Of Bmp09 With Bk Channel-mentioning
confidence: 99%
“…2b) (Cotton et al 1997;Dauplais et al 1997;Gendeh et al 1997b;Tudor et al 1996). Two-dimensional 1 H NMR studies have shown that the SAK-I toxins secondary structure is mainly characterized by two short α-helices without β-sheet and belongs to the αα-type of fold (Dauplais et al 1997;Mouhat et al 2004;Tudor et al 1996). These toxins do not share structure homologies in sequence and disulfide pairings with scorpion (e.g.…”
Section: Sea Anemone K + Channel Toxin Structuresmentioning
confidence: 99%
“…Only two other peptides are known to block ERG type channels: ErgTx1 and BeKm-1, two scorpion toxins isolated from Centruroides noxius and Buthus eupeus venoms, respectively. These scorpion toxins belong to the Csαβ fold family characterized by a α-helix linked by disulfide bridges to a triple-stranded β-sheet (Bontems et al 1991;Mouhat et al 2004). ErgTx1 and BeKm display different species-specific effects and affinities for the three neuronal members of ERG channel Kv3.1 Kv3.2 Kv3.3 Kv3.4 Fig.…”
Section: Effect Of Sak-iii Toxins On Different Subfamilies Of Kv Chanmentioning
confidence: 99%
“…[71][72] Such type of fold is found in the classes of human -defensins ( Figure 3) and scorpion toxins that target Na + -channels. 73 Thus crotamine shares the functional properties of cell penetration with most CPPs and the structural characteristics with the classes of both membrane-active peptides: AMPs and CPPs. However, any antimicrobial activity was yet attributed to crotamine.…”
Section: Cell Penetrating Peptides and Crotaminementioning
confidence: 99%